PENGARUH STRATEGI DIGITAL MARKETING DAN BRAND IMAGE TERHADAP LOYALITAS PELANGGAN APLIKASI TIKTOK SHOP PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIKARTA - kartina Eka Ningsih; Johansyah Johansyah; Syahruddin S Syahruddin S; Sandy Febian Sakti; Salman Alfarisi (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2025)
The purpose of this study was to determine the effect of digital marketing and brand image variables simultaneously on customer loyalty for the TikTok Shop application for students of the Faculty of Economics and Business, Unikarta. This study uses quantitative data obtained from questionnaire data. The number of research samples was 52 people with the method of taking by random sampling. The analysis tool uses multiple regression analysis and hypothesis testing using the F test and t test. From the ANOVA or F test, the calculated F value is 97.584, while the table F value is 2.79. This means that (F calculated 97.584 > F table 2.79) with a significance level of 0.000 < 0.05, so it can be concluded that the variables of digital marketing and brand image together have a significant influence on customer loyalty to the TikTok Shop application among students. Based on the coefficient b value, it shows that the digital marketing variable has the most dominant influence on customer loyalty (0.603) followed by the brand image variable (0.499).